The Effect Of The Training System On Employee Performance Improvement At The Office Of The Statistics At Labuhan Batu Regency - Maya Amelia; Muhammad Irwan Padli Nasution (Penerbit Jurnal Indonesia, 2022)
The purpose of the study was to determine how the influence of the training system on improving employee performance at the Central Bureau of Statistics in Labuhan Batu Regency. The method used in this research is quantitative research in the form of a survey, which is a study in which data and information are obtained from a large number of resource persons. The population of this research is employees from various divisions who work at the BPS office in Labuhan Batu district as many as 25 people. The sampling technique used is the census technique, namely conducting research on the entire existing population. The results of this study are that there is an effect of training on employee performance at the Central Bureau of Statistics of Labuhan Batu Regency.